2021
DOI: 10.3390/ijerph18041890
|View full text |Cite
|
Sign up to set email alerts
|

An Application of a Hybrid Intelligent System for Diagnosing Primary Headaches

Abstract: (1) Background: Modern medicine generates a great deal of information that stored in medical databases. Simultaneously, extracting useful knowledge and making scientific decisions for diagnosis and treatment of diseases becomes increasingly necessary. Headache disorders are the most prevalent of all the neurological conditions. Headaches have not only medical but also great socioeconomic significance. The aim of this research is to develop an intelligent system for diagnosing primary headache disorders. (2) Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Considering the incompleteness of the language rules used when human experts express knowledge, a study used the Learning-From-Examples algorithm to improve correct recognition rate [ 20 ]. Another study developed a hybrid intelligent system for diagnosing primary headache disorders, applying various mathematical, statistical, and artificial intelligence techniques [ 21 ]. Although various tools have been developed to improve the diagnostic algorithm, no computer-assisted systems have obtained headache information directly from the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the incompleteness of the language rules used when human experts express knowledge, a study used the Learning-From-Examples algorithm to improve correct recognition rate [ 20 ]. Another study developed a hybrid intelligent system for diagnosing primary headache disorders, applying various mathematical, statistical, and artificial intelligence techniques [ 21 ]. Although various tools have been developed to improve the diagnostic algorithm, no computer-assisted systems have obtained headache information directly from the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is possible to use hybrid intelligent approaches [28] or ML decision trees to realise systems that are able to make a reliable diagnosis of primary or secondary headache based on ICH-3 criteria [1]. The results of a cross-sectional study on 202 patients showed how a Computer-based Diagnostic Engine (CDE) proved to be a reliable tool compared to a semi-structured interview performed by a headache specialist.…”
Section: Improving Diagnosismentioning
confidence: 99%
“…Such classification could improve patient management, influencing the physician's approach based on the main pain pattern reported by the patient. Simic, 2021 [28] Various mathematical, statistical, and artificial intelligence techniques, including decision-making methodology and clustering methods…”
Section: Improving Classificationmentioning
confidence: 99%
“…The author of this research developed a hybrid intelligent system for diagnosing primary headaches. In their path of research they incorporated various methods like Calinski-Harabasz, Analytical hierarchy process, and weighted fuzy-Cmeans algorithms to give qualitative and expected experiment outcomes that help to make quality decisions for further treatments (16) . The research work carried out to identify the optimal number of clusters has used 21 different datasets which have selective features to demonstrate the similarity of each other.…”
Section: Literature Reviewmentioning
confidence: 99%